2012
DOI: 10.1016/j.ajhg.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

RBPJ Mutations Identified in Two Families Affected by Adams-Oliver Syndrome

Abstract: Through exome resequencing, we identified two unique mutations in recombination signal binding protein for immunoglobulin kappa J (RBPJ) in two independent families affected by Adams-Oliver syndrome (AOS), a rare multiple-malformation disorder consisting primarily of aplasia cutis congenita of the vertex scalp and transverse terminal limb defects. These identified mutations link RBPJ, the primary transcriptional regulator for the Notch pathway, with AOS, a human genetic disorder. Functional assays confirmed im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 26 publications
6
87
0
2
Order By: Relevance
“…Consistent with our data, it is reported that mutations in human RBPJ may lead to skin telangiectasias, which are small vascular malformations directly under the surface of the skin (Hassed et al, 2012). Currently, known genetic lesions account for very few human AVM cases (Young and Yang, 2004), and it is of upmost clinical interest to describe and investigate novel molecular mechanisms of AVM formation and progression.…”
Section: Deletion Of Endothelial Rbpj Results In Vascular Abnormalitisupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with our data, it is reported that mutations in human RBPJ may lead to skin telangiectasias, which are small vascular malformations directly under the surface of the skin (Hassed et al, 2012). Currently, known genetic lesions account for very few human AVM cases (Young and Yang, 2004), and it is of upmost clinical interest to describe and investigate novel molecular mechanisms of AVM formation and progression.…”
Section: Deletion Of Endothelial Rbpj Results In Vascular Abnormalitisupporting
confidence: 73%
“…Human patients with mutations in RBPJ are affected by AdamsOliver syndrome and may present with cardiovascular anomalies and/or skin telangiectasias (Hassed et al, 2012). Given that the expression of a Notch gain-of-function mutation in the endothelium just after birth reprograms the molecular identity of arterial and venous ECs and leads to abnormal AV shunts in immature mouse brains, and that loss of endothelial Notch during embryogenesis also reprograms the AV identity of ECs and results in AV anastomoses, we tested whether Notch signaling is required in postnatal endothelium to maintain AV organization and AV marker expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutations in human EOGT have been reported in an autosomal recessive form of a human disease called AdamsOliver syndrome (55,56). Notably, mutations in several Notch pathway components cause an autosomal dominant form of the same disease (39,40,(57)(58)(59). Together, these reports provide strong evidence that O-GlcNAcylation might modulate Notch signaling.…”
Section: Eics Of O-glucose Sites Represented By Peptides Also Containsupporting
confidence: 50%
“…AOS can be caused also by dominant mutations in RBPJ (MIM 147183), a transcriptional regulator of the NOTCH signaling pathway, further demonstrating the genetic heterogeneity of the phenotype. 5 As some features of AOS are consistent with vascular disruption pathogenesis, 2 it is yet unclear how disrupted Cdc42/Rac1 or NOTCH signaling intersects in the pathogenesis of AOS. Identification of additional genes implicated in AOS might elucidate common molecular pathways leading to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It is noteworthy that F-actin staining in our EOGT mutant fibroblasts showed apparently intact cell cytoskeleton and morphology. There is growing evidence that the AOS phenotype might be mediated through the NOTCH signaling pathway: AOS-causing RBPJ mutations are assumed to effect NOTCH signaling, 5 and drosophila Notch ligands Delta and Serrate, as well as mammalian Notch1 are O-GlcNAc-modified by Eogt. 8,11 Moreover, heterozygosity for either Notch or for several members of the canonical Notch signaling pathway suppresses wing blistering formation caused by Eogt knockdown in drosophila.…”
mentioning
confidence: 99%